Teachers' Strategies in Instilling Tolerance in Early Childhood - Ria, Cut Salfitri; Hijriati, Hijriati (STAI Publisistik Thawalib Jakarta, 2025)
Early childhood education is crucial for instilling empathy, tolerance, and social values through creative methods, while Aceh Flexi School addresses inclusion challenges with teacher strategies and training to foster harmony. This study examines teachers’ strategies in fostering tolerance and the challenges faced in the learning environment. Using a qualitative case study, it explores teachers’ methods through interviews, observations, and documentation, validated by source and method triangulation. Results show teachers use adaptive, contextual, and experiential approaches, introducing diversity via stories, play, and cooperation. Strategies are tailored to children’s character, emphasizing healthy social interaction and positive emotions. Teachers model inclusivity and fairness, supported by the learning environment and parental involvement. Challenges include external influences, child conflicts, and limited facilities and training. Children need time to adjust. Teachers overcome obstacles through restorative approaches, experiential learning, and emotional support. The synergy among school, children, and community strengthens tolerance practices despite limited resources. In conclusion, fostering tolerance in children requires adaptive approaches, direct experience, and environmental support, with active roles from teachers, parents, and the community to overcome challenges and build inclusive character. Submission November 27, 2024 Revised January 19, 2025 Accepted April 17, 2025 Publish 05 May, 2025